2016
DOI: 10.3389/fmicb.2016.00991
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Dysbiosis: Rethinking Disease in Marine Ecosystems

Abstract: With growing environmental pressures placed on our marine habitats there is concern that the prevalence and severity of diseases affecting marine organisms will increase. Yet relative to terrestrial systems, we know little about the underlying causes of many of these diseases. Moreover, factors such as saprophytic colonizers and a lack of baseline data on healthy individuals make it difficult to accurately assess the role of specific microbial pathogens in disease states. Emerging evidence in the field of medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
174
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(176 citation statements)
references
References 93 publications
(102 reference statements)
1
174
0
1
Order By: Relevance
“…Which pathogens or scavengers will dominate then depends on stochastic or environmental processes resulting in communities with high variability between events or samples. This theory is in line with the emerging view that many important environmental and medical diseases are the result of a disruption of the normal microbiome (dysbioses) and that multiple opportunistic pathogens, rather than single aetiological agents, are driving diseases (Burge et al ., ; Egan and Gardiner, ; Hajishengallis and Lamont, ). Indeed we have recently demonstrated that bleaching of D. pulchra under laboratory conditions can be induced by multiple and taxonomically distinct bacterial pathogens, resulting in dysbioses of the normal microbiome (Kumar et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Which pathogens or scavengers will dominate then depends on stochastic or environmental processes resulting in communities with high variability between events or samples. This theory is in line with the emerging view that many important environmental and medical diseases are the result of a disruption of the normal microbiome (dysbioses) and that multiple opportunistic pathogens, rather than single aetiological agents, are driving diseases (Burge et al ., ; Egan and Gardiner, ; Hajishengallis and Lamont, ). Indeed we have recently demonstrated that bleaching of D. pulchra under laboratory conditions can be induced by multiple and taxonomically distinct bacterial pathogens, resulting in dysbioses of the normal microbiome (Kumar et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the methodological caveats mentioned above, the current analysis gives some evidence for this as bleaching‐enriched bins complement each other in order to provide more of the bleaching‐enriched genes. The suggestion that multiple pathogens contribute to bleaching disease is consistent with the polymicrobial synergy and dysbiosis (PSD) model of infectious disease, which has been developed to explain human periodontal disease (Hajishengallis and Lamont, ) and is increasingly being used to explain several other medical and environmental diseases (Burge et al ., ; Egan and Gardiner, ; Hajishengallis and Lamont, ). In contrast to conventional infectious diseases, which are caused by a single or a few selected pathogens, diseases that fit the PSD model are caused by a dysbiotic, synergistic microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…While host-microbiome symbiosis and dysbiosis has been mostly considered in humans and humanized models (Hamdi et al, 2011;Nicholson et al, 2012;Scharschmidt and Fischbach, 2013), many of the same concepts are applicable to organisms in the sea (Egan and Gardiner, 2016), and are being explored in various systems (discussed below). The exact factors and mechanisms tipping the scale between symbiosis and dysbiosis will probably vary with complexity of the host anatomy and immune functioning (e.g., simplistic sponges and corals compared to more complex fish and sharks) as well as with the complexity of interactions that may occur between the members of the microbiome.…”
Section: Conceptual Model Of Factors Contributing To Host-microbiome mentioning
confidence: 99%
“…Corals can harbor complex microbial ecosystems, which frequently result in the development of both specific and variable host‐associated microbial communities (reviewed in Webster & Reusch, ), which can benefit host fitness (Peixoto, Rosado, Leite, Rosado, & Bourne, ; Webster & Reusch, ). Despite the close relationship between corals and their associated microbiomes, which can include organisms that have effects that vary from beneficial (Damjanovic, Blackall, Webster, & van Oppen, ; Krediet, Ritchie, Paul, & Teplitski, ; Peixoto et al., ; Webster & Reusch, ) to pathogenic (Meistertzheim, Nugues, Quéré, & Galand, ; Sweet & Bulling, ; Wright et al., ), knowledge of these intrinsic symbiotic, or dysbiotic, that is, disrupted symbiotic relationships (Bosch & Miller, ; Egan & Gardiner, ; Petersen & Round, ), interactions, and associated mechanisms is sparse.…”
Section: Introductionmentioning
confidence: 99%